Deteksi Dini Kanker Ovarium Menggunakan International Ovarian Tumor Analysis (IOTA) - Sania Utari; Renardy Reza Razali (Universitas Malahayati, 2026)
ABSTRACT Ovarian cancer is one of the most lethal gynecological malignancies, with approximately 70% of cases diagnosed at an advanced stage. It ranks as the fourth leading cause of cancer-related deaths among women. The prognosis of ovarian cancer improves significantly when detected early, but the disease is often asymptomatic in its initial stages, leading to delayed diagnosis and poorer outcomes. Because of its low cost and accessibility, ultrasound has proved to be the most useful diagnostic tool for adnexal masses. Ultrasound can be used to distinguish benign from malignant adnexal masses using IOTA simple rules. Early detection of ovarian cancer is important for reducing mortality from ovarian cancer. A case report of Mrs. SW, a 34-year-old woman came to Arifin Achmad Hospital who presented with palpable of abdominal mass. The patient underwent a series of diagnostic tests, including physical examination, ultrasound, abdominal CT scan, and histopathology. On ultrasound examination, found an adnexal mass suspected ovarian cancer by using International Ovarian Tumor Analysis (IOTA). The IOTA simple rules describe five typical features of benigna (B) tumours and five typical features of malignant (M) tumours. It had high sensitvity and specificity for discriminating between malignant and benign adnexal tumour. Preoperative diagnose of malignant adnexal mass using IOTA simple rules were confirmed by postoperative pathology analysis shown a bilateral fibrosarcoma ovary. Early diagnosis is important for reducing mortality from ovarian cancer. Imaging techniques, such as ultrasound (US) have been used in the preoperative assessment of adnexal tumours. IOTA simple rules can distinguish benign from malignant adnexal masses. It can provide an important reference for clinical decision making. Keywords: Ovarian Cancer, International Ovarian Tumor Analysis (IOTA), Adnexal Mass.